Why Are Long Rates Sensitive to Monetary Policy? - Tore Ellingsen; Ulf Söderström (Sveriges Riksbank, 2004)
We use a quantitative model of the U.S. economy to analyze the response of long-term interest rates to monetary policy, and compare the model results with empirical evidence. We find that the strong and time-varying yield curve response to monetary policy innovations found in the data can be explained by the model. A key ingredient in explaining the yield curve response is central bank private information about the state of the economy or about its own target for inflation.
Keywords: E43; E52; 330; Term structure of interest rates; Yield curve; Central bank private information; Excess sensitivity